2019
DOI: 10.1155/2019/6973932
|View full text |Cite|
|
Sign up to set email alerts
|

Nav1.7 via Promotion of ERK in the Trigeminal Ganglion Plays an Important Role in the Induction of Pulpitis Inflammatory Pain

Abstract: The trigeminal ganglion (TG) refers to sensory neurons bodies that innervate the spinal cord and peripheral axons that innervate teeth. The tetrodotoxin-sensitive sodium (NA) channels (Nav1.7) play important roles in the pathophysiology of pain. In this study, we investigated the TG expression of Nav1.7 and extracellular signal-regulated kinase (ERK) in a rat model of pulpitis to explore the correlation between these channels and inflammatory pain. Pulpitis was confirmed by hematoxylin-eosin staining. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Among them, one ∼500-kb duplication covering the serine-threonine kinase MAPK3 was shared by the proband and the affected mother, but not the unaffected father in family TRGN190. MAPK3 has been previously implicated in the pathogenesis of multiple trigeminal pain models ( Alter et al., 2010 ; Liverman et al., 2009 ; Smyth et al., 2003 ; Sun et al., 2019 ). Interestingly, the TRGN190 proband with the MAPK3 duplication was diagnosed with bilateral cTN-1 at 11 years of age and exhibited bilateral NVC on brain magnetic resonance imaging (MRI).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, one ∼500-kb duplication covering the serine-threonine kinase MAPK3 was shared by the proband and the affected mother, but not the unaffected father in family TRGN190. MAPK3 has been previously implicated in the pathogenesis of multiple trigeminal pain models ( Alter et al., 2010 ; Liverman et al., 2009 ; Smyth et al., 2003 ; Sun et al., 2019 ). Interestingly, the TRGN190 proband with the MAPK3 duplication was diagnosed with bilateral cTN-1 at 11 years of age and exhibited bilateral NVC on brain magnetic resonance imaging (MRI).…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the case of MAP3K1 (Mitogen-Activated Protein Kinase Kinase Kinase 1), this gene encodes a serine/threonine kinase and has been shown to be part of many signaling transduction cascades including ERK (extracellular signal-regulated kinases) [30] and JNK (c-Jun N-terminal kinase) kinase [31], NF-kappa B [32], TLR4 signaling [33], and IL-1 family signaling pathways [32]. Since these pathways mentioned here have been verified to be implicated in pulpitis [34][35][36], MAP3K1 can be speculated to be also involved in pulpal inflammation. Taking the case of HIF1A (hypoxia-inducible factor 1 subunit alpha), this gene encodes the alpha subunit of transcription factor hypoxia-inducible factor-1 (HIF-1) [37].…”
Section: Discussionmentioning
confidence: 81%
“…Most subtypes that have been included in this pain pathway are Nav1.7, Nav1.8, and Nav1.9 ( Fang et al, 2002 ; Luo et al, 2010 ). Among these channel subtypes, the expression of Nav1.7 increased in various chronic pain states ( Dib-Hajj et al, 2007 ; Sun et al, 2019 ). Consistent with the results of previous studies, our investigation also confirmed that the expression level of Nav1.7 in TGs was upregulated in the pulpitis state.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in primary afferent nerve fibers result in increased excitability, which causes hyperalgesia ( Byers and Närhi, 1999 ). These functional changes may be manipulated by specific signaling components in neurons ( Sun et al, 2019 ). Ectopic neuronal activity triggered by increasing sensitization is coincident with changes in the expressions of several ion channels and receptors ( Julius and Basbaum, 2001 ; Davies et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation